2004
DOI: 10.1073/pnas.0308746101
|View full text |Cite
|
Sign up to set email alerts
|

NGEP, a gene encoding a membrane protein detected only in prostate cancer and normal prostate

Abstract: We identified a gene (NGEP) that is expressed only in prostate cancer and normal prostate. The two NGEP transcripts are 0.9 kb and 3.5 kb in size and are generated by a differential splicing event. The short variant (NGEP-S) is derived from four exons and encodes a 20-kDa intracellular protein. The long form (NGEP-L) is derived from 18 exons and encodes a 95-kDa protein that is predicted to contain seven-membrane-spanning regions. In situ hybridization shows that NGEP mRNA is localized in epithelial cells of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 17 publications
5
74
0
Order By: Relevance
“…Suzuki et al, 2010;Castoldi et al, 2011 TMEM16G Expression in prostate cancer and normal prostate. Bera et al, 2004;Das et al, 2007 TMEM16K Mutation found in autosomal-recessive cerebellar ataxia. Vermeer et al, 2010 12 and cancer.…”
Section: Tmem16amentioning
confidence: 99%
See 1 more Smart Citation
“…Suzuki et al, 2010;Castoldi et al, 2011 TMEM16G Expression in prostate cancer and normal prostate. Bera et al, 2004;Das et al, 2007 TMEM16K Mutation found in autosomal-recessive cerebellar ataxia. Vermeer et al, 2010 12 and cancer.…”
Section: Tmem16amentioning
confidence: 99%
“…RNA analysis revealed two splice variants of TMEM16G mRNA: a short form encoding a soluble protein and a long form encoding a polytopic membrane protein. Overexpression of TMEM16G in the prostate cancer cell line LNCaP promotes formation of large cell aggregates (Bera et al, 2004;Das et al, 2007). However, the exact role of TMEM16G in prostate is unknown.…”
Section: Transmembrane Protein 16a Family Members and Disease Corrmentioning
confidence: 99%
“…Similar to ANO1, ANO7 has a role in cancer, specifically prostate cancer (Bera et al, 2004). A set of dominant mutations in ANO5 was linked to the rare skeletal condition gnathodiaphyseal dysplasia (Tsutsumi et al, 2004), whereas recessive mutations were found to lead to limbgirdle muscular dystrophy or Miyoshi myopathy (Bolduc et al, 2010).…”
Section: Caccs and Human Diseasementioning
confidence: 99%
“…Although a deeper understanding is currently lacking, it should be mentioned that various anoctamins have a role during murine embryogenesis [9]. Ano7 (TMEM17G, NGEP) has been detected in prostate cancer [52,53]. Studies indicate that the long version of NGEP is present on the plasma membrane of overexpressing LNCaP cells and is highly concentrated at cell-cell contact regions [53].…”
Section: Other Anoctamins Correlated To Cancermentioning
confidence: 99%